Analysis of the Influence of Mudharabah Financing, Musyarakah Financing, Capital Adequacy Ratio, and Non-Performing Financing on Banking Performance with Qardhul Hasan as Control Variable (Case Study on Islamic Commercial Banks in Indonesia in 2013-2017) - Alfiyah, Mike Ayu; Widiastuti, Ekaningtyas; Sudarto, Sudarto (Indonesian Journal of Islamic Business and Economics (IJIBE), 2023)
This research entitled "Analysis of the Influence of Mudharabah Financing, Musyarakah Financing, Capital Adequacy Ratio (CAR), and Non-Performing Financing (NPF) on Banking Performance with Qardhul Hasan as Control Variable (Case Study in Sharia Commercial Banks in Indonesia 2013-2017)". The purpose of this research is to analyze the influence of Mudharabah Financing, Musyarakah Financing, CAR, and NPF against Banking Performance with Qardhul Hasan as a Control Variable and to know the variables that have a dominant influence on Banking Performance in Sharia commercial banks that were recorded in the Financial Services Authority in 2013-2017. The population of this research is Sharia commercial banks listed by the Financial Services Authority in 2013-2017. The total population is 13, and eight samples were obtained using purposive sampling. The type of this research is quantitative research associated with panel data regression analysis techniques. Based on the analysis results, it is found that Mudharabah Financing does not affect Return On Assets. Musyarakah Financing does not affect Return On Assets. Capital Adequacy Ratio does not affect Return On Assets, and Non-Performing Financing has a negative effect on Return On Assets. This research implies that banks are expected to pay more attention to the level of capital adequacy and management of problematic financing to increase profitability.